PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN TERHADAP KUALITAS LAPORAN KEUANGAN - Purwaniati Nugraheni; Imam Subaweh (Jurnal Ilmiah Ekonomi Bisnis, 2011)
The objectives of this study are to (i) analyze the effect of level of knowledge ofUAPPA E1 and UAPPB officers towards Government Accounting Standard (SAP) onfinancial statements quality; (ii) analyze the effect of the availability of facilities andinfrastructures supporting the implementation of SAP on financial statements quality;and (iii) investigate level of improvement of financial statements quality years 2007and 2008 compared with financial statements quality year 2006. The Office ofInspectorate General of the Department of National Education was selected as theobject in this study. A set of valid and reliable questionnaires were used in this study.Multiple linier regression analysis was applied to analyze the data. The study resultsshowed that the implementation of SAP, level of knowledge of UAPPA E1 andUAPPB, and the availability of facilities and infrastructures have significant impactson financial statements quality.